Characterization of methanol degrading bacteria and their roles in promoting algal growth - Lim, Jia Rong (2017)
Algal blooms occur when there is a large increase in concentrations of algae. Such high concentrations of algae in the environment may be detrimental to other organisms. Interactions between algae and bacteria may be a factor which promotes algal growth. It was found that the availability of nutrients provided to the algae such as phosphorus and nitrogen plays an important role in affecting the algal growth and some bacteria were reported to have the ability to solubilize phosphate and fix nitrogen.